Vitamin D Receptor Activation Reduces Angiotensin-II–Induced Dissecting Abdominal Aortic Aneurysm in Apolipoprotein E–Knockout Mice. Issue 8 (August 2016) - Martorell, Sara; Hueso, Luisa; Gonzalez-Navarro, Herminia; Collado, Aida; Sanz, Maria-Jesus; Piqueras, Laura
Abstract : Objective—: Abdominal aortic aneurysm (AAA) is a vascular disorder characterized by chronic inflammation of the aortic wall. Low concentrations of vitamin D3 are associated with AAA development; however, the potential direct effect of vitamin D3 on AAA remains unknown. This study evaluates the effect of oral treatment with the vitamin D3 receptor (VDR) ligand, calcitriol, on dissecting AAA induced by angiotensin-II (Ang-II) infusion in apoE −/− mice. Approach and Results—: Oral treatment with calcitriol reduced Ang-II–induced dissecting AAA formation in apoE −/− mice, which was unrelated to systolic blood pressure or plasma cholesterol concentrations. Immunohistochemistry and reverse-transcription polymerase chain reaction analysis demonstrated a significant increase in macrophage infiltration, neovessel formation, matrix metalloproteinase-2 and matrix metalloproteinase-9, chemokine (CCL2 [(C-C motif) ligand 2], CCL5 [(C-C motif) ligand 5], and CXCL1 [(C-X-C motif) ligand 1]) and vascular endothelial growth factor expression in suprarenal aortic walls of apoE −/− mice infused with Ang-II, and all were significantly reduced by cotreatment with calcitriol. Phosphorylation of extracellular signal–regulated kinases 1/2, p38 mitogen-activated protein kinase, and nuclear factor-κB was also decreased in the suprarenal aortas of apoE −/− mice cotreated with calcitriol. These effects were accompanied by a marked increase in VDR–retinoid X receptor (RXR) interaction in the aortas of calcitriol-treated mice. In vitro, VDR activation by calcitriol in human endothelial cells inhibited Ang-II–induced leukocyte–endothelial cell interactions, morphogenesis, and production of endothelial proinflammatory and angiogenic chemokines through VDR–RXR interactions, and knockdown of VDR or RXR abolished the inhibitory effects of calcitriol. Conclusions—: VDR activation reduces dissecting AAA formation induced by Ang-II in apoE −/− mice and may constitute a novel therapeutic strategy to prevent AAA progression. Abstract : Supplemental Digital Content is available in the text.